Receipt of tobacco direct mail/email discount coupons and trajectories of cigarette smoking behaviours in a nationally representative longitudinal cohort of US adults. Issue 3 (19th June 2018) - Choi, Kelvin; Chen, Julia Cen; Tan, Andy S L; Soneji, Samir; Moran, Meghan B
Abstract : Background: We assessed whether receipt of coupons—via direct mail or e-mail—was prospectively related to trajectories of smoking behaviours. Methods: Data were from a cohort of US adults (n=26 447) who participated in wave 1 (2013–2014) and wave 2 (2014–2015) of the Population Assessment of Tobacco and Health Study. Participants reported receipt of tobacco direct mail/email coupons in the past 6 months in wave 1 and their smoking status in both waves. Weighted multiple logistic regressions were used to examine demographic correlates of receiving tobacco direct mail/email coupons at wave 1 and to examine the prospective effect of receiving tobacco coupons on trajectories of smoking behaviours. Findings: At wave 1, 10.7% of never smokers, 13.9% of experimental smokers, 37.1% of current smokers and 16.5% of former smokers reported receiving tobacco direct mail/email coupons. Lower education and higher poverty adults and non-Hispanic white current smokers were more likely to have received these coupons (p<0.05). Receiving tobacco direct mail/email coupons at wave 1 was associated with increased odds of smoking initiation among never smokers (adjusted odds ratio (AOR)=2.28, 95% CI 1.36 to 3.83), becoming established smokers among experimenters (AOR=1.62, 95% CI 1.29 to 2.04), becoming daily smokers among non-daily smokers (AOR=1.56, 95% CI 1.23 to 1.99) and smoking relapse among former smokers between waves (AOR=1.91, 95% CI 1.39 to 2.65). Receiving these coupons at wave 1 was associated with reduced odds of smoking cessation ≥6 months among current smokers (AOR=0.71, 95% CI 0.58 to 0.88). Conclusions: Tobacco direct mail/email coupons encourage and sustain smoking and disproportionately affect lower socioeconomic populations.